Implementasi Kepribadian Guru dalam Pembentukan Karakter Religiusitas Santri Pondok Pesantren Saifullah, Batu Gemuk, Namorambe, Deli Serdang Sumatera Utara - Amir Panatagama; Asmaji Mochtar; Toha Makhshun (Journal on Education, 2025)
Teachers are at the forefront of implementing education. It is imperative for teachers to realize their position as the nation's light, to be role models and to provide enlightenment. This study aims to determine the Implementation of Teacher Personality in the Formation of Religious Character of Students at Saifullah Islamic Boarding School, to find out the obstacles and challenges in fostering the Personality of Teachers at Saifullah Islamic Boarding School, and to find out the efforts of teachers in overcoming obstacles and challenges in fostering the Personality Competence of Teachers at Saifullah Islamic Boarding School. The research method is qualitative which is descriptive in nature, which is the instrument or tool of the researcher himself, the data obtained from two sources, namely primary sources and secondary sources with data collection techniques through observation, interviews and documentation. The data analysis technique is carried out inductively. The results of the study indicate that the Implementation of Teacher Personality in the Formation of Religious Character of Students at Saifullah Islamic Boarding School Batu Gemuk, Namorambe, Deli Serdang, North Sumatra Alhamdulillah is good. This can be seen from a) The stability and steadfastness of the teacher's soul in carrying out tasks in class and optimism towards the success of students and teacher activities outside the classroom, b) The maturity of the teacher in guidance activities for students and the teacher's attitude in guiding students and the teacher's attitude in dealing with problematic students, c) The teacher's wisdom and prudence in attending evaluation meetings and the teacher's consideration in giving punishment to students d) The teacher's authority is seen from the ability to guide students and their skills in motivating students, e) The teacher's discipline in entering the class and the teacher's discipline in dressing and the teacher's attitude in responding to students' clothing, f) The teacher's ability to provide values ​​and the teacher's efforts in developing themselves.